KNOWLEDGE AND PRACTICE OF EMERGENCY NURSES REGARDING TRIAGE - MUSHTAQ , S; SADDIQUE , H; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Effective triage is essential for prioritizing patients and ensuring optimal resource allocation in emergency departments. Emergency nurses play a vital role in this process, yet gaps in their knowledge and practices can hinder patient outcomes: Objective: To assess the knowledge and practices of emergency nurses regarding triage in a tertiary care hospital in Lahore, Pakistan Methods: A descriptive cross-sectional study was conducted among 150 emergency nurses using a structured questionnaire. Data were analyzed using SPSS version 26, with results presented as frequencies and percentages. Results: The study revealed that 35.3% of nurses had low knowledge, 16% had moderate knowledge, and 34% demonstrated high knowledge of triage. Regarding practices, 54% of participants exhibited poor adherence to triage protocols, while 46% demonstrated good practices. Nurses with higher qualifications and more experience showed significantly better knowledge and practices. Conclusion: This study identifies critical gaps in the knowledge and practices of emergency nurses regarding triage. Targeted training, institutional support, and the implementation of standardized triage guidelines are necessary to enhance the efficiency and effectiveness of emergency care in Pakistan.